2018
DOI: 10.1508/cytologia.83.125
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Rearrangement: From Induction by Heavy-Ion Irradiation to <i>in Vivo</i> Engineering by Genome Editing

Abstract: Chromosomal rearrangements are thought to play a role in speciation, adaptation and evolution. The effects of chromosomal rearrangements on gene expression have been reported in many species and their close relatives, and may illustrate the consequences of adaptation. To investigate the effects of chromosomal rearrangements on phenotypic changes directly, studies of experimentally induced rearrangements are required; they allow gene expression and epigenetic states to be compared between mutants and wild-types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…For instance, disruption of TAGs was achieved by induction of large deletions using g-ray irradiation (Morita et al, 2007) as a forward genetic approach and Zinc Finger Nucleases as a reverse genetic approach (Qi et al, 2013). It has been also reported that C-ion or Ar-ion beam with higher LET value at 290 keV mm -1 can induce deletions ranging from several hundred bp to several Mbp, which are large enough to disrupt TAGs (Hirano et al, 2012(Hirano et al, , 2015Kazama et al, 2018;Abe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, disruption of TAGs was achieved by induction of large deletions using g-ray irradiation (Morita et al, 2007) as a forward genetic approach and Zinc Finger Nucleases as a reverse genetic approach (Qi et al, 2013). It has been also reported that C-ion or Ar-ion beam with higher LET value at 290 keV mm -1 can induce deletions ranging from several hundred bp to several Mbp, which are large enough to disrupt TAGs (Hirano et al, 2012(Hirano et al, , 2015Kazama et al, 2018;Abe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy-ion beams have also been used for mutation breeding and functional studies as a powerful physical mutagen (Abe et al 2015;Hirano et al 2022;Kazama et al 2018;Tanaka et al 2010;Yamaguchi 2018). Linear energy transfer (LET; keV µm −1 ) is the amount of energy that an ionizing particle transfers to the material traversed per unit distance and is used as an index for expressing the radiation quality.…”
Section: Introductionmentioning
confidence: 99%
“…The heavy-ion beam is a type of ionizing radiation and is composed of accelerated ions heavier than helium. Thus far, mutation-inducing techniques using heavy-ion beams have been developed mainly in plants (Tanaka et al 2010;Kazama et al 2018;Abe et al 2021;Hirano et al 2022). One of the characteristics of heavy-ion beams is their high linear energy transfer (LET, keV µm 1 ), which is a unit of energy deposited per unit length along the pass of the radiation through a substance.…”
mentioning
confidence: 99%